Nuclear 80S Ribosomes Present Across the Stages of Cell Cycle in Drosophila Melanogaster Cells - Akilu Abdullahi; Saverio Brogna (UMYU Journal of Microbiology Research)
Nuclear translation has been a subject of controversy between scientists for over 5 decades. Despite the existence of evidence to the contrary, most biologists agree that translation exclusively takes place in the cytoplasm of eukaryotes.  In recent years, more evidences are being presented that disprove this theory. Here we employed the Ribo-BiFC technique which can detect assembled, and potentially translating, ribosomes invivo and studied nuclear 80S assembly and translation at all the stages of cell cycle in Drosophila S2 cells. The results obtained suggest that 80S ribosomes are present in the nucleus particularly within the nucleolus across all the cell cycle stages in Drosophila S2 cells that were visualised. The signal observed is more apparent in S-phase. This investigation supports the many other previous findings that nuclear translation may occur in eukaryotic organisms.